Competency of Midwives in Assisting Vaginal Breech Births and associated factors: A Cross-sectional study in Lower Level Health Facilities of Hoima District, Uganda. - Prossy Nandawula; Ayebare Elizabeth; Mathew Nyashanu; Michelle Telfer; Scovia Nalugo Mbalinda (Student's Journal of Health Research Africa, 2022)
Objectives: